Pengaruh Layanan Konseling Kelompok Dengan Teknik Mindfulness Terhadap Peningkatan Flow Akademik Peserta Didik Di MAN 1 Bandar Lampung: Pengaruh Layanan Konseling Kelompok Dengan Teknik Mindfulness Terhadap Peningkatan Flow Akademik Peserta Didik Di MAN 1 Bandar Lampung - kasandra dewi sartika Dewi Sartika (Advice: Jurnal Bimbingan dan Konseling, 2026)
This study was motivated by the low level of academic flow among students, which is characterized by lack of concentration in learning, low engagement in learning activities, and difficulty maintaining focus on academic tasks. Academic flow is a positive psychological condition that allows students to be optimally involved in learning activities. One effort that can be made to improve academic flow is through group counseling services using midnfulness techniques. This study aims to determine the effect of group counseling services using midnfulness techniques on improving students’ academic flow at MAN 1 Bandar Lampung. The research method used was a quantitative approach with a pre-experimental design using the One Group Pretest–Posttest Design. The research sample consisted of 10 students from class XI IIS 2 selected using purposive sampling techniques. Data collection techniques included academic flow questionnaires, observation, and documentation. The data were analyzed using statistical tests to determine the differences between pretest and posttest scores. The results showed that there was a significant increase in students’ academic flow after receiving group counseling services with midnfulness techniques. This is indicated by the increase in the average posttest score compared to the pretest score. Thus, it can be concluded that group counseling services with midnfulness techniques have an effect on improving students' academic flow at MAN 1 Bandar Lampung.